Rose meets Mr. Wintergarten - Graham, Bob, 1942- (Cambridge, Mass. : Candlewick Press, 1992)
A young girl's attempt to retrieve her ball from her grouchy, old neighbor's yard changes the way they feel about each other
Accelerated Reader AR
Keywords: Neighborliness -- Fiction; Old age -- Fiction